A facile one-pot synthesis of hyper-branched carbazole-based polymer as a hole-transporting material for perovskite solar cells. Issue 14 (20th March 2017) - Zhou, Zhonggao; Zhao, Yan; Zhang, Chunlei; Zou, Ding; Chen, Yunxiang; Lin, Zhenghuan; Zhen, Hongyu; Ling, Qidan
Abstract : A novel hyper-branched carbazole-based polymer is synthesized and used as hole-transporting material for PVSCs giving a PCE of 14.07%. Abstract : A low-cost, hyper-branched, carbazole-based polymer (HB-Cz) was designed and synthesized by a facile "A3 + B2" one-pot Suzuki polycondensation reaction. Due to the hyper-branched structure and carbazole unit, HB-Cz is a promising candidate for a hole-transporting material, which was confirmed in perovskite solar cells (PVSCs) with a configuration of ITO/TiO2 /MAPbI3 /HB-Cz/Ag. The films of poly-(3-hexylthiophene) and linear poly[ N -(1-octylnonyl)-9 H -carbazole-2, 7-diyl] were also used as hole-transporting layers (HTLs) in the reference devices. Time-resolved photoluminescence spectra indicate that HB-Cz has the fastest charge regeneration. Electrochemical impedance spectroscopy revealed that HB-Cz could reduce carrier recombination effectively, improving the open circuit voltage and fill factor of the PVSCs. A PCE of 14.07% obtained from the HB-Cz-based device was much higher than those of devices based on P3HT (9.05%) and PCz (6.60%), and this is attributed to the superior hole-transporting property and surface smoothing effect of the HB-Cz HTL.